Evaluation of The Use of Pregnancy Monitoring Charts by Village Cadres & PKK, A Case Study - Subagyo Martodipuro (Paediatrica Indonesiana, 1984)
The use of pregnant monitoring chart by recording weight gain during pregnancy can be as an indicator of the growth of the fetus. It is easily measurable, simple, easy to undertake even by layman and can be use I to select high risk pregnancies in the field. Using the chart, the selection to give supplemental food to pregnant mothers can be conducted objectively. If the health center has the capability and the resources to do Hb examination, urinalysis, immunization and proper prenatal care, untowards effects for the mother and fetus can be avoided. With minimal promotive care, i.e. distribution of Fe tablets in the 3rd trimester and supplemental calorie for those who need it, the incidence of low birth weight can be reduced. Village cadres & PKK can be trained to use pregnant monitoring charts and are very effective to obtain a total coverage of pregnant women, since they live in the same location and know each other. With these activities the mother, do not need to go to the health centers, which may be far away. The operation of mobile health centers or subcenters will be supported by this activity. Although in this case study, the use of pregnancy monitoring charts did proof to reduce the incidence of low birth weights, yet the author suggests to try these charts in other areas.